The Effect of Tax Fairness Perception on Tax Avoidance Intentions among Individual Taxpayers in Manado City - Yahya, Mohammad Rizky (Journal of Economics and Social Sciences (JESS), 2025)
This study investigates the effect of tax fairness perception on the intention to avoid taxes among individual taxpayers in Manado City, Indonesia. In the broader context of persistent tax compliance challenges in developing countries, this research focuses on the behavioral dimension of taxation, particularly the role of perceived fairness in shaping taxpayer decisions. The objective of this study is to determine whether various dimensions of tax fairness—horizontal fairness, vertical fairness, ability to pay, exchange fairness, procedural fairness, and interpersonal fairness—significantly influence taxpayers’ intentions to engage in tax avoidance. A quantitative approach was employed using a structured questionnaire distributed to 100 individual taxpayers, with responses analyzed through binary logistic regression. The dependent variable, tax avoidance intention, was classified into a binary outcome (intends vs. does not intend), while the independent variables comprised eight items representing tax fairness perception. The findings reveal that only one dimension, fair treatment by tax officers (interpersonal fairness), has a statistically significant effect on tax avoidance intention (p = 0.011), with an odds ratio of 0.153, indicating a strong negative relationship. Other dimensions did not demonstrate significant influence, and some were omitted from the model due to perfect prediction issues. The results suggest that interpersonal interactions and ethical conduct of tax officials play a more immediate and impactful role in influencing taxpayer behavior than broader structural or policy-related aspects of tax fairness. This study underscores the importance of service quality and fairness in tax administration and offers practical insights for policymakers seeking to enhance voluntary tax compliance through behavioral approaches.